2016
DOI: 10.1128/jvi.01124-16
|View full text |Cite
|
Sign up to set email alerts
|

Myristoylation of the Arenavirus Envelope Glycoprotein Stable Signal Peptide Is Critical for Membrane Fusion but Dispensable for Virion Morphogenesis

Abstract: Arenaviruses are responsible for severe and often fatal hemorrhagic disease. In the absence of effective antiviral therapies and vaccines, these viruses pose serious threats to public health and biodefense. Arenaviruses enter the host cell by fusion of the viral and endosomal membranes, a process mediated by the virus envelope glycoprotein GPC. Unlike other class I viral fusion proteins, GPC retains its stable signal peptide (SSP) as an essential third subunit in the mature complex. SSP spans the membrane twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 69 publications
3
22
0
Order By: Relevance
“…Interestingly, we found that A168 had reverted to the wild-type T168 in 55% of reads. This back-mutation was previously noted upon serial passage of the ΔG2-GPC rCan mutant in standard cell culture medium (28), suggesting that the presence of the N166 glycan enhances virus fitness in cell culture. The V353A substitution in GP2 (39% of reads) is also noteworthy due to its proximity to the I347F change noted upon passage of K33S-GPC rCan in the absence of AmCl.…”
Section: K33s-gpc Rcan Retains K33s and F427i Upon Prolonged Passage supporting
confidence: 62%
See 3 more Smart Citations
“…Interestingly, we found that A168 had reverted to the wild-type T168 in 55% of reads. This back-mutation was previously noted upon serial passage of the ΔG2-GPC rCan mutant in standard cell culture medium (28), suggesting that the presence of the N166 glycan enhances virus fitness in cell culture. The V353A substitution in GP2 (39% of reads) is also noteworthy due to its proximity to the I347F change noted upon passage of K33S-GPC rCan in the absence of AmCl.…”
Section: K33s-gpc Rcan Retains K33s and F427i Upon Prolonged Passage supporting
confidence: 62%
“…After 10 passages, the p10 virus was subjected to RNA-Seq. Other than the previously noted A-to-T transversion in the S RNA 3=-UTR (28), no additional nucleotide changes were identified ( Table 2). The stability of rCan perhaps is not surprising because Candid#1 had been extensively passaged in Vero cells.…”
Section: K33s-gpc Rcan Retains K33s and F427i Upon Prolonged Passage mentioning
confidence: 65%
See 2 more Smart Citations
“…First, the N-terminal myristoylation of SSP, although not critical for assembly, trafficking, nor localization with specific lipid domains of the cell surface, [141,185] is critical for fusion with host cell membranes [191]. Second, the penultimate C-terminal C57 is a critical contributor of a zinc-finger motif in the cytoplasmic tail of GP2, which is required to secure the SSP with the GPC [186,192,193].…”
Section: The Stable Signal Peptide -Sspmentioning
confidence: 99%